Expanding the Scope of Azole-Based γ-Amino Acids – Synthesis and Structural Diversity - Chaise, Samantha; Gacogne, Audrey; Garcin, Ilan; de Figueiredo, Renata Marcia; Campagne, Jean-Marc; Legrand, Baptiste; Maillard, Ludovic T. (Synthesis, 2025)
The development of non-canonical amino acids is pivotal to peptide engineering, enabling the design of molecules with novel structural features, improved activities, and optimized metabolic profiles. Among these, heteroaromatic γ-amino acids have attracted significant attention for their ability to mimic native peptide folds while accessing novel conformational spaces. In this study, the chemical diversity of heteroaromatic γ-amino acids was expanded by introducing two new monomers, ATC* and AOC*, designed around a thiazole and an oxazole scaffold, respectively. These analogues, characterized by their tunable substitution patterns and precise stereochemical control significantly expand the well-established ATC family.
Keywords: γ-amino acid; heterocycles; azole scaffold; peptide engineering; peptidomimetic; solid-phase synthesis